Ecological based environmental Kuznets curve for Africa: Evidence from the fishery sector at continental, regional and country-specific levels - Andrew Phiri; Danai Tembo (Cogent Economics & Finance, 2023)
The purpose of our study is to examine the Fishery-based Environmental Kuznets Curve (EKC) for a sample of 48 African countries between 1970-2019. We estimate cubic EKC-type models using quantile regression to account for distributional asymmetries existing in the time series data, and our empirical analysis is conducted at continental, regional and country-specific levels. Methodologically, our findings indicate that most EKC relationships are found at the tail-end of the quantile regressions, hence demonstrating their usefulness in capturing "hidden relationships" amongst the variables. Empirically, our findings reveal that Southern African countries along the Atlantic Ocean, as well as West African countries which lie along the Gulf of Guinea, tend to have exploitable Fishery-EKC. Conversely, conflict-prone countries found along the Mediterranean Sea, the Indian Ocean and landlocked nations either have inverse or non-existent Fisheries EKC. We provide a novel theoretical explanation for our findings and offer policy recommendations for different stakeholders in African Fisheries markets.
Keywords: 330; Africa; country-specific analysis; economic development; Environmental Kuznets Curve (EKC); Fisheries; quantile regressions; regional analysis